Salicylanilide diethyl phosphates as potential inhibitors of some mycobacterial enzymes - Krátký, Martin; Novotná, Eva; Saxena, Shalini; Yogeeswari, Perumal; Sriram, Dharmarajan; Švarcová, Markéta; Vinšová, Jarmila (TheScientificWorldJournal, 2014)
Antimycobacterially active salicylanilide diethyl phosphates were evaluated to identify their potential drug target(s) for the inhibition of several mycobacterial enzymes, including isocitrate lyase, L-alanine dehydrogenase (MtAlaDH), lysine ε-aminotransferase, chorismate mutase, and pantothenate synthetase. The enzymes are related to the nongrowing state of Mycobacterium tuberculosis. Salicylanilide diethyl phosphates represent new candidates with significant inhibitory activity especially against L-alanine dehydrogenase. The most active MtAlaDH inhibitor, 5-chloro-2-[(3-chlorophenyl)carbamoyl]phenyl diethyl phosphate, has an IC50 of 4.96 µM and the best docking results. Other mycobacterial enzymes were mostly inhibited by some derivatives but at higher concentrations; isocitrate lyase showed the highest resistance to salicylanilide diethyl phosphates.
Keywords: Mycobacterium tuberculosis; Bacterial Proteins; Salicylanilides; salicylanilidy; Antitubercular Agents; antituberkulotika; simulace molekulového dockingu; bakteriální proteiny; Molecular Docking Simulation; Enzyme Inhibitors; inhibitory enzymů